The WITS Atlas: A Black Southern African dental atlas for permanent tooth formation and emergence. Issue 1 (15th February 2018) - Esan, Temitope A.; Schepartz, Lynne A.
Abstract: Current dental maturity charts, such as the widely applied London atlas, do not take into consideration advanced tooth emergence and formation patterns observed in children of African ancestry. The result is inaccurate age estimation in Southern Africa, a region where there is great forensic and anthropological need for reliable age estimation. Objectives: To develop a population‐specific atlas of permanent tooth emergence and formation for age estimation of Black Southern Africans. Materials and Methods: Using data from a cross‐sectional study of 642 school children aged 5–20 years, panoramic radiographs taken during routine dental examination in a mobile treatment van were analyzed using the Demirjian method of eight (A–H) tooth formation stages. Tables of the stages of tooth development for each tooth, including the third molars, were generated separately for age cohorts and by sex. The most frequently occurring (modal) stage of tooth formation was considered the signature developmental stage for the age. The relationship of the third molar occlusal surfaces with occlusal tables on the radiographs were checked and compared with the findings recorded during intra oral examination. Results: Comparison with the London atlas shows that at age 9.5 years, the canine and premolar emergence are at least one year ahead and the third molar formation completes four years earlier in the WITS Atlas. Discussion: Similarities in advancement in tooth formation and emergence across sub‐Saharan Africa suggest that the WITS Atlas can be used for those populations as well.